Stress Attributes for Indian Orthodontic Practitioners: A Cross-sectional Study - Riddhi Patel; Ajay K. Kubavat; Khyati V. Patel; Priyal Bhavsar; Vishwa Sejani; Anuj Patel (Wolters Kluwer Medknow Publications, 2024)
Background: Because orthodontists work long hours and maintain a relationship with each patient for many years prior to the end of treatment, they may encounter unusually stressful situations. Materials and Methods: A self-administered, anonymous survey was disseminated to orthodontic residents and practitioners in India. The survey includes 29 probable stressors. Result: Over 61% of respondents opined that these factors are the most stressful in orthodontic practice.